Evaluation of the Anatomical and Optical Characteristics of the Eye in the Clinical Course of Congenital Myopia - Batirovich, Khamrakulov Sobir (American Journal of Bioscience and Clinical Integrity, 2025)
Evaluation of morphofunctional parameters of the visual analyzer with an increase in the length of the anterior-posterior axis (APA) of the eye in patients with myopia. Materials and methods: The study included 36 patients (71 eyes). All patients in the study were divided into 4 groups according to the size of the anterior-posterior axis of the eyeball. The first group consisted of patients with mild myopia and an axial length of 23.81 to 25.0 mm; the second - patients with moderate myopia and an axial length of 25.01 to 26.5 mm; the third - patients with high myopia, an axial length value of more than 26.51 mm; the fourth group - patients with refraction close to emmetropic and an axial length of 22.2 to 23.8 mm. In addition to a standard ophthalmological examination, the following diagnostic complex was performed on the patients: echobiometry, determination of the optical density of the macular pigment (ODMP), digital photography of the fundus, optical coherence tomography of the anterior and posterior segments of the eyeball. Results: The average age of the patients was 47.3±13.9 years. During the statistical processing of the obtained results of the studied parameters, a decrease was noted in some of them with an increase in axial length: maximum corrected visual acuity (p=0.01), sensitivity in the infraorbital region (p=0.008), average retinal thickness in the infraorbital region (p=0.01), average in the choroidal and nasal sectors p=0.05. 03). In addition, a significant statistically reliable inverse correlation was found between PZO and (BCVA) -0.4 in all groups of subjects; also, the thickness of the infraorbital region was 0.6; choroidal thickness in the infraorbital region -0.5 and sensitivity -0.6; (p<0.05). Conclusion: A detailed analysis of the obtained average values of the studied parameters revealed a general tendency to decrease in the morphofunctional indicators of the eyeball with increasing AOV in the groups. Correlation data obtained from the clinical test indicate a close relationship between the morphometric and functional parameters of the visual analyzer.